Regulation of human lymphocyte response in vitro by monocytes and their subsets - Zembala, M; Pryjma, J; Uracz, W; Kowalczyk, D; Ruggiero, I; Mytar, B (Folia biologica, 1986)
This paper summarizes the observations on functional heterogeneity of human peripheral blood monocytes (MO). MO are required as accessory cells in lymphoproliferative responses in vitro, but they also inhibit such responses when added in large numbers. Most of human MO express Fc receptors (FcR), but a minority of MO do not possess these receptors as assessed by functional assays. Isolated FcR+ and FcR- MO subsets differ in their functional properties. The FcR+ MO are mostly responsible for the suppression of lymphoproliferation and cytostatic activity against tumour targets, while FcR- MO possess strong antigen-presenting capacity and also the ability to stimulate auto- and allo-MLR. The FcR- MO subset is enriched in cells expressing HLA-DQ determinants, and their ability to present antigen is blocked by anti-DQ but not by anti-DR monoclonal antibodies. In long-term cultures the FcR+ but not FcR- MO induce suppressor T cells which then inhibit antigen-driven lymphoproliferation. PWM-induced Ig synthesis in vitro is enhanced when FcR- MO are added at the beginning of culture. In contrast, FcR+ MO suppress this response possibly by arresting terminal differentiation of B lymphocytes into immunoglobulin-secreting cells and there is some evidence that OKT8 positive T (T8+) lymphocytes are involved. These observations suggest that the regulation of the lymphocyte response by MO is a complex phenomenon in which the ratio of functional different subsets may be important. This may be critical for understanding the altered function of MO in human diseases. Our previous observations suggest that MO of some cancer patients possess an increased suppressor activity, and the presence of suppressor MO is a favourable prognostic factor. A further delineation of functional MO subsets should facilitate a better understanding of the role of MO in immunoregulation.
Keywords: cytotoxické T-lymfocyty; imunoglobulin G; HLA-DR Antigens; Histocompatibility Antigens Class II; Neoplasms; erytrocyty; nádory; Cytotoxicity, Immunologic; Lymphocyte Activation; aktivace lymfocytů; lidé; cytotoxicita imunologická; monocyty; protilátky anti-idiotypické; mitogeny líčidla amerického; T-lymfocyty; Immunoglobulins; Immunoglobulin G; Receptors, Fc; Monocytes; T-Lymphocytes, Cytotoxic; T-Lymphocytes, Regulatory; Erythrocytes; Pokeweed Mitogens; receptory Fc; T-Lymphocytes; imunoglobuliny; HLA-DR antigeny; HLA-DQ Antigens; regulační T-lymfocyty; MHC antigeny II. třídy; HLA-DQ antigeny; Antibodies, Anti-Idiotypic; Humans